SISTEM INFORMASI GEOGRAFIS BERBASIS ANDROID KANTOR DINAS PEMERINTAH KOTA BAUBAU - Mohamad Arif Suryawan; La Raufun La Raufun; Herlin Herlin (Prodi Teknik Informatika Unidayan Baubau, 2022)
The Baubau City regional office is one of the regional apparatuses as an assistant element to the mayor and the Regional People's Representative Council (DPRD) in the administration of government affairs which are the regional authority of Baubau City. The Baubau City government office has 23 service offices spread throughout the Baubau City area with their respective roles and duties. The spread of office locations can make it difficult for the people of Baubau City and immigrant communities to find the location of the official office and information on the official office. Therefore, a geographic information system for mapping the Baubau City government office is needed. This study aims to design an android-based geographic information system application for mapping the Baubau City government office. The data used in this study is collected data on maps of the Baubau City area using Mapbox and leaflets js, interviews at each office address, collecting data on coordinate points, and some other supporting data. This research produces an application that can make it easier for users to find the location of official offices and display office information in the form of office names, addresses, coordinate points, telephone numbers, emails, websites, office pictures, and routes to the Baubau City government offices.